Basin Modelling Using GIS - Ahmad Saffian Bin Ahmad Husni, Ahmad Saffian (Universiti Teknologi Petronas, 2010)
The aim of this projet is to locate potential hydrocarbons area by overlaying the elements of hydrocarbons accumulation simultaneously in GIS software. It is not reliable to locate a potential hydrocarbon reserves based on a single data of an clement only in a single time